2016
DOI: 10.3389/fpls.2016.01199
|View full text |Cite
|
Sign up to set email alerts
|

The Garlic Allelochemical Diallyl Disulfide Affects Tomato Root Growth by Influencing Cell Division, Phytohormone Balance and Expansin Gene Expression

Abstract: Diallyl disulfide (DADS) is a volatile organosulfur compound derived from garlic (Allium sativum L.), and it is known as an allelochemical responsible for the strong allelopathic potential of garlic. The anticancer properties of DADS have been studied in experimental animals and various types of cancer cells, but to date, little is known about its mode of action as an allelochemical at the cytological level. The current research presents further studies on the effects of DADS on tomato (Solanum lycopersicum L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 97 publications
8
33
0
1
Order By: Relevance
“…The GH3 genes encode a group of enzymes that adenylate IAA or conjugate free IAA with amino acids, thereby inhibiting plant growth. In the present study, the elevated expression of SAURs and decreased expression of GH3 suggest that DADS promotes auxin content, consistent with a previous study19. In addition, auxin could induce the production of H 2 S, which promotes lateral root formation in tomato45.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The GH3 genes encode a group of enzymes that adenylate IAA or conjugate free IAA with amino acids, thereby inhibiting plant growth. In the present study, the elevated expression of SAURs and decreased expression of GH3 suggest that DADS promotes auxin content, consistent with a previous study19. In addition, auxin could induce the production of H 2 S, which promotes lateral root formation in tomato45.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study, we demonstrated that DADS exerts a biphasic, dose-dependent effect on tomato primary root elongation; DADS promoted tomato root elongation at low concentrations (0.01–0.62 mM) but inhibited elongation at high concentrations (6.2–20.67)19. Based on previous studies, we propose that DADS may also play an important role in alleviating the obstacles to continuous cropping of vegetables.…”
mentioning
confidence: 73%
“…However, higher doses of RGS inhibited eggplant growth, chlorophyll contents, and most photosynthesis attributes in both years. Garlic reportedly contains organosulfur compounds such as DADS (diallyl disulfides), diallyl trisulfide (DATS), and allicin (strong antioxidants), which at higher concentrations inhibit plant growth and photosynthesis by decreasing chlorophyll contents and root length [38,39]. Similar results were observed in our study in the case of RGS3.…”
Section: Effect Of Rgs On Plant Growthsupporting
confidence: 89%
“…It has been recognized that allelochemicals could be released from plants into the environment through several ways such as volatilization, root exudation, decomposition and leaching to interfere the growth of adjacent plants (Subrahmaniam et al ., 2018). Some allelochemicals could increase cell membrane permeability (Bais et al ., 2003; Chai et al ., 2013), inhibit cell division and elongation, damage cell sumicroscopic structure (Teerarak et al ., 2012; Cheng et al ., 2016), disturb plant photosynthesis and respiration (Yu et al ., 2005), affect synthesis of plant endogenous hormones and proteins (Zeng et al ., 2001; Hu et al ., 2015), and so on. In consequence, allelopathy would potentially influence the growth and development of plants, succession of plant communities (Cummings et al ., 2012; Bonanomi et al ., 2018) and invasion of exotic plant into forest ecosystems (Meiners et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%